Peningkatan Kualitas Pembelajaran Melalui Kegiatan Supervisi Klinis - Amu Katharina (Ekspektasi: Jurnal Pendidikan Ekonomi, 2020)
The aim this researcher is to find out the improvement in the quality of learning among IPI Ende elementary school teachers thtough clinical supervision. This type of research used is school action research. The subject in this study were 6 IPI Ende elementary school teachers. Data collection techniques are through observation, documentation and interviews. Based on the results of this study it can be concluded that clinical supervision can improve the quality of learning among teachers at IPI Ende Elementary School.